A highly effective fireproof silicone rubber compound and its preparation method and application

By using composite porcelain fillers of copper oxide, gallium oxide and titanium dioxide in silicon rubber mixing glue, as well as composite porcelain fillers of antimony trioxide and bismuth trioxide, combined with aluminum hydroxide flame retardant fillers and boron-containing organosiloxane, the problem of poor porcelain formation effect of ceramic silicone rubber under high temperature flame impact was solved, and a hard, dense and high-strength ceramic body was formed at a high temperature of 1600-1750℃.

CN117551351BActive Publication Date: 2025-03-28HANGZHOU NORMAL UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311535977.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-03-28
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

The existing ceramic silicone rubber has poor porcelain formation effect under high-temperature flame impact, the porcelain body is prone to cracking, and its vibration resistance is poor, making it difficult for the surface of the fire-resistant silicone rubber to form a hard, dense and continuous flame-retardant ceramic layer, and its fire resistance performance is poor at higher temperatures (1600-1750℃).

Method used

The composite porcelain filler of copper oxide, gallium oxide and titanium dioxide, as well as the composite porcelain filler of antimony trioxide and bismuth trioxide, combined with aluminum hydroxide flame retardant filler and boron-containing organosiloxane, are optimized to improve the raw material composition and preparation method of silicone rubber mixing glue to improve the porcelain formation effect of silicone rubber at high temperatures.

Benefits of technology

A hard, dense and high-strength ceramic body is formed at a high temperature of 1600 to 1750°C. It can maintain the integrity and mechanical strength of the ceramic body after flame attack for 30 minutes, significantly improving the mechanical properties after ablation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004554997320000031
    Figure BDA0004554997320000031
  • Figure BDA0004554997320000131
    Figure BDA0004554997320000131
  • Figure BDA0004554997320000141
    Figure BDA0004554997320000141
Patent Text Reader

Abstract

The present invention discloses a highly efficient fireproof silicone rubber compound and its preparation method and application. The present invention optimizes the composition and dosage of raw materials. Copper oxide, titanium dioxide and gallium oxide are combined to form a composite ceramic filler, and antimony trioxide and bismuth trioxide are combined to form a composite ceramic filler, which can reduce the amount of ceramic filler, and cooperate with aluminum hydroxide flame retardant filler, boron-containing organic siloxane and short-cut high-silica fiber to improve the ceramic effect of silicone rubber at high temperature, improve the strength of the ceramic body after ablation, improve the problem of poor mechanical properties after ablation, and obtain a hard, dense and high-strength ceramic body at a higher temperature of 1600-1750°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone rubber materials, and in particular to a highly efficient fireproof silicone rubber compound and a preparation method and application thereof. Background Art

[0002] Silicone rubber is a semi-inorganic polymer rubber elastomer with Si-O-Si as the main chain. It has a series of excellent properties, such as high and low temperature resistance, weather resistance, ozone resistance, arc resistance, electrical insulation, resistance to certain chemicals, high air permeability and physiological inertness.

[0003] When silicone rubber burns, there is no melt dripping, slow burning speed, low heat release rate and no toxic gas release. However, after burning, the silicon dioxide powder generated by silicone rubber loses its supporting function and falls off, and cannot achieve continuous fire protection under continuous flame attack. Ceramic silicone rubber, as a new type of high-temperature fireproof material, is an effective way to achieve fire retardancy of silicone rubber at high temperatures. At room temperature, its performance is the same as that of ordinary rubber materials, but when it is at high temperature, it can form a dense and hard inorganic ceramic body to prevent the spread of flames. The ceramic silicone rubber ceramic principle is that when silicone rubber encounters open flame attack or high temperature, its matrix part first undergoes "organic-inorganic" decomposition to produce amorphous SiO2 powder. When the temperature rises to the softening point of the flux, the flux melts to form a liquid phase filled between the ceramic filler (or ceramic filler) and the SiO2 powder. As the temperature rises, the ceramic filler and the SiO2 powder can be more fully penetrated and bonded to each other under the "bridging" effect of the flux to form a hard, dense and complete ceramic body.

[0004] The traditional method is usually to add a large amount of ceramic fillers to the matrix to make the silicone rubber better ceramicized; but excessive ceramic fillers not only reduce its compatibility with silicone rubber, damage the mechanical properties, and are not conducive to processing and molding, but also seriously affect the strength of the ceramic body after the silicone rubber is ablated, resulting in poor fire resistance. With the development of new technology fields, higher requirements are put forward for ceramic silicone rubber fireproof materials in many occasions to achieve efficient ceramicization at a lower density. There is an urgent need for fireproof materials with excellent ablation resistance and flame retardancy, and can withstand longer and higher temperature flame attacks. The rubber itself is required to have good mechanical strength and high mechanical strength after ceramicization.

[0005] Ceramic silicone rubber has excellent flame retardancy, ablation resistance, heat insulation, weathering resistance, electrical insulation, etc., and is widely used in new energy, aerospace, construction, power equipment and other fields. Ceramic silicone rubber plays a key role in improving fire safety and efficient flame retardancy and fire prevention. However, the current ceramicization effect of fire-retardant silicone rubber is poor under the impact of high-temperature flames, the porcelain body will crack, and the poor vibration resistance will cause it to fall off, making it difficult to form a hard, dense and continuous flame-retardant ceramic layer on the surface of the fire-retardant silicone rubber. Therefore, higher requirements are put forward for high-performance flame retardant and fireproof materials, which need to meet higher fire protection temperatures (1600-1750°C) and have higher mechanical strength after ceramicization.

[0006] Chinese patent document CN115538175A discloses a flame retardant, heat-insulating and fireproof material for batteries. The silicone rubber flame retardant and heat-insulating material provided by the patent technology includes a flame retardant and heat-insulating layer and an impact-resistant layer. The impact-resistant layer is a composite of multiple layers of glass fiber cloth; the flame retardant and heat-insulating layer includes 40 to 60 parts of silicone rubber, 10 to 17 parts of incremental filler, 20 to 30 parts of porcelain filler, 15 to 25 parts of flame retardant, 2 to 10 parts of glass powder, and 2 to 5 parts of additives. The incremental filler is any one of diatomite, wollastonite, calcium carbonate and fumed silica or a combination of at least two; the ceramic filler is any one of muscovite, phlogopite, kaolin, brucite and talc or a combination of at least two; the flame retardant is any one of antimony trioxide, aluminum hydroxide, magnesium hydroxide, phosphorus-containing inorganic flame retardant, boron-containing inorganic flame retardant and phosphorus-containing organic flame retardant or a combination of at least two; the glass powder is any one of silicon oxide, boron oxide and metal oxide or a combination of at least two; the auxiliary agent includes silane coupling agent, silicone oil and vulcanizing agent. The flame retardant heat-insulating fireproof material provided by the patented technology is compounded with the flame retardant heat-insulating layer through glass fiber cloth to improve the impact resistance of the fireproof material, thereby forming a dense ceramic layer that does not fall off under the impact of 1500℃ flame.

[0007] Chinese patent document CN113829701A discloses a ceramic flame retardant heat insulation fireproof material and its preparation method and application, wherein the ceramic flame retardant heat insulation fireproof material comprises a flame retardant heat insulation layer and a substrate layer which are bonded to each other; the substrate layer is made of glass fiber cloth; the flame retardant heat insulation layer is made of a rubber compound; the rubber compound comprises the following raw material components in parts by weight: 30 to 40 parts of organic silicone rubber, 15 to 30 parts of ceramic filler, 15 to 22 parts of incremental filler, 15 to 21 parts of flame retardant and 1 to 6 parts of flux. The incremental filler comprises a combination of diatomaceous earth, wollastonite, calcium carbonate and fumed silica; the ceramic filler is selected from any one or a combination of at least two of muscovite, phlogopite, kaolin, brucite and talc; the flame retardant comprises a combination of aluminum hydroxide, magnesium hydroxide, phosphorus-containing inorganic flame retardant and phosphorus-containing organic flame retardant; the flux comprises a combination of glass powder and boron compound. This fireproof material can withstand the impact of acetylene flame and oxygen up to 1500°C through the synergistic effect of glass fiber cloth and substrate layer, and obtain a complete ceramic body without cracks after combustion. However, this patented technology adds a large amount of filler and fails to break through the flame retardancy at higher temperatures (such as 1600°C). Summary of the invention

[0008] In the first aspect, the present invention provides a highly efficient fireproof silicone rubber compound, which optimizes the composition and dosage of raw materials. Copper oxide, titanium dioxide and gallium oxide are combined to form a composite porcelain filler, and antimony trioxide and bismuth trioxide are combined to form a composite porcelain-aiding filler, which can reduce the dosage of porcelain-forming fillers, and cooperate with aluminum hydroxide flame-retardant fillers and boron-containing organic siloxanes to improve the porcelain-forming effect of silicone rubber at high temperatures. The porcelain-aiding filler can continuously provide a molten body at high temperatures to ensure that the "bridging" between the filler and the silica powder plays the maximum role, and solid-state sintering occurs to generate high-temperature resistant materials, enhance the ablation resistance, and the short-cut high-silica fiber plays a "skeleton" reinforcement role, so that the integrity and density of the ceramic body are higher, the strength of the ceramic body after ablation is improved, and the problem of poor mechanical properties after ablation is improved, and a hard, dense, and high-strength ceramic body is obtained at a higher temperature of 1600-1750°C.

[0009] A highly effective fireproof silicone rubber compound, the raw material composition of which is calculated by weight:

[0010]

[0011] The porcelain-forming filler comprises:

[0012] 3-9 parts of copper oxide,

[0013] 5 to 12 parts of titanium dioxide,

[0014] 4-12 parts of gallium oxide;

[0015] The porcelain-aiding filler comprises:

[0016] 3-15 parts of antimony trioxide,

[0017] 3-15 parts of bismuth trioxide;

[0018] The flame retardant filler includes aluminum hydroxide;

[0019] The high temperature resistant fiber comprises short chopped high silica fiber; the short chopped high silica fiber is a glass fiber containing more than 95wt% of silica and having a length of 1 to 12mm;

[0020] The preparation method of the boron-containing organosiloxane comprises the steps of:

[0021] (1) adding acid water with a pH value of 3 to 4 to a mixed solution of silane and toluene, and reacting at 50 to 70° C.; the water content in the acid water is 15% to 30% of the amount of water theoretically required for complete reaction of the silane; the silane includes methylphenyldimethoxysilane and dimethyldiethoxysilane;

[0022] (2) After the reaction in step (1) is completed, the upper layer of acid water is removed, and then toluene, phenylboric acid and hexamethyldisiloxane are added and reacted at 70-90° C. After the reaction is completed, the layers are washed with water and the organic phase is taken and distilled under reduced pressure to remove the solvent to obtain the boron-containing organosiloxane.

[0023] The end-capping groups of the boron-containing organosiloxane of the present invention are hydroxyl and / or methyl. When hexamethyldisiloxane is not added in step (2), the end-capping is hydroxyl. When hexamethyldisiloxane is added in step (2), the end-capping is performed with both hydroxyl and methyl groups, or all of the end-capping is performed with methyl groups.

[0024] The boron-containing organosiloxane of the present invention can treat highly active hydroxyl groups in fillers such as white carbon black, improve the structuring phenomenon of the rubber compound, and can improve the compatibility of various fillers and fillers, and fillers and substrates. When the silicone rubber compound is attacked by high-temperature flames, the boron-containing organosiloxane will be pyrolyzed and oxidized to produce boron oxide. Boron oxide has a low melting point and plays a fluxing role in the ceramic process. It begins to melt above 450°C to form a high-viscosity glassy substance, which plays a high-temperature bonding role, improves the ceramic forming ability of silicone rubber, and reduces the generation of pores. In addition, boron oxide participates in free radical reactions, inhibits the formation of free radicals, plays a flame retardant and fireproof role, and boron oxide and silicon dioxide generate borosilicate ceramic bodies, which have better high temperature resistance and reduce smoke density. As the flame temperature increases, the synergistic effect of various filler additives is more fully carried out, the ceramic formation is more complete and dense, and a ceramic body with higher strength is obtained, and the ablation temperature can reach up to 1750°C.

[0025] In a preferred embodiment, the mass fraction of copper oxide is 4 to 8 parts.

[0026] In a preferred embodiment, the mass fraction of titanium dioxide is 6 to 11 parts.

[0027] In a preferred embodiment, the mass fraction of antimony trioxide is 3 to 12 parts.

[0028] In a preferred embodiment, the mass fraction of bismuth trioxide is 3 to 12 parts.

[0029] In a preferred embodiment, the mass fraction of gallium oxide is 5 to 11 parts.

[0030] In a preferred embodiment, the sum of the mass fractions of copper oxide, titanium dioxide and gallium oxide is 15 to 30 parts.

[0031] In a preferred embodiment, the sum of the mass fractions of antimony trioxide and bismuth trioxide is 6 to 24 parts.

[0032] The mass fraction of aluminum hydroxide may be 15 to 30. Of course, the flame retardant filler may also include other metal hydroxides such as magnesium hydroxide.

[0033] The mass fraction of the short-cut high-silica fiber may be 1 to 5. Of course, the high-temperature resistant fiber may also include carbon fiber, silicon carbide fiber, and the like.

[0034] In one embodiment, the molar ratio of Si to B in the boron-containing organosiloxane is 1-5:1.

[0035] In step (1), the mole percentage of the methylphenyldimethoxysilane in the silane may be 15% to 25%, and the mole percentage of the dimethyldiethoxysilane in the silane may be 75% to 85%.

[0036] In step (1), in the mixed solution of silane and toluene, the mass of the toluene is 40% to 60% of the mass of the silane.

[0037] In step (1), the reaction time may be 3 to 5 hours.

[0038] In step (2), the mass of toluene added may be 40% to 60% of the mass of the silane.

[0039] In step (2), the molar ratio of the added phenylboric acid to the silane can be 1:1-4, preferably 1:1-3.

[0040] In step (2), the molar ratio of the added hexamethyldisiloxane to the silane can be 0 to 0.05:1. For example, when preparing a methyl-terminated boron-containing organosiloxane, the molar ratio can be 0.025 to 0.05:1, 0.035 to 0.045:1, etc.

[0041] In step (2), the temperature of the reduced pressure distillation can be 60-80°C.

[0042] The molar content of vinyl in the methyl vinyl silicone rubber may be 0.03% to 3%.

[0043] In one embodiment, the molecular weight of the methyl vinyl silicone rubber is 45×10 4 ~85×10 4 g / mol.

[0044] The molar content of vinyl in the methyl vinyl phenyl silicone rubber is 0.1-0.5%, and the molar content of phenyl can be 30%-40%.

[0045] In one embodiment, the molecular weight of the methyl vinyl phenyl silicone rubber is 40×10 4 ~80×10 4 g / mol.

[0046] The white carbon black may be precipitated white carbon black and / or fumed white carbon black.

[0047] The specific surface area of ​​the white carbon black can be 120 to 420 m 2 / g, preferably 120 to 220 m 2 / g.

[0048] In one embodiment, the structuring control agent includes hydroxy silicone oil. The hydroxy silicone oil may have a hydroxyl mass content of 4% to 10%, preferably 4% to 8%.

[0049] The release agent may include a stearic acid compound.

[0050] In a second aspect, the present invention provides a method for preparing the silicone rubber compound described in the first aspect, comprising the steps of:

[0051] S1, adding methyl vinyl silicone rubber, methyl vinyl phenyl silicone rubber, white carbon black and a structure control agent into a kneader for internal kneading;

[0052] S2, adding porcelain-forming filler, porcelain-assisting filler, flame-retardant filler, high-temperature resistant fiber, boron-containing organic siloxane and release agent for internal mixing;

[0053] S3, raising the temperature of the kneading machine cabin to 80-160°C, kneading and mixing at a constant temperature under a negative pressure environment of -0.03-0.08 MPa to obtain the silicone rubber compound.

[0054] In step S1 and step S2, the white carbon black, the flame retardant filler, the ceramic filler, the boron-containing organosiloxane, the methyl vinyl silicone rubber, and the methyl vinyl phenyl silicone rubber are fully and evenly mixed by banburying in a kneader for a sufficient time. The structuring control agent and the boron-containing organosiloxane are synergistically effective to avoid the structuring phenomenon caused by the addition of white carbon black and the ceramic filler, and to ensure the processability and storage stability of the silicone rubber compound. At the same time, an appropriate amount of a release agent is used to reduce the phenomenon of the silicone rubber compound sticking to the roller.

[0055] The purpose of maintaining the mixing at 80-160° C. in step S3 is to improve the compatibility and distribution of the filler in the raw rubber, improve the fluidity of the silicone rubber compound, achieve better processing plasticity, and reduce the roller sticking phenomenon.

[0056] The purpose of constant temperature mixing in the negative pressure environment of -0.03 to -0.08 MPa in step S3 is to remove small molecules in the silicone rubber, moisture in white carbon black and low boiling point by-products produced during mixing, so as to obtain a silicone rubber compound with more stable performance.

[0057] In step S1, white carbon black can be added to the kneader in batches for multiple times and evenly filled into the silicone rubber as a reinforcing filler.

[0058] The mixing time in step S1 may be 40 to 90 minutes.

[0059] The mixing time in step S2 may be 40 to 120 minutes.

[0060] In step S3, after the temperature of the kneading machine cabin is raised to 80-160°C, the constant temperature kneading time can be 60-80 minutes.

[0061] The highly efficient fireproof silicone rubber compound provided by the present invention uses methyl vinyl silicone rubber and methyl vinyl phenyl silicone rubber as the basic raw materials, and adds white carbon black as a reinforcing filler to improve the mechanical properties of silicone rubber. At the same time, in order to avoid the structuring phenomenon caused by adding reinforcing fillers and porcelain-forming fillers, an appropriate amount of structuring control agent is added to cooperate with boron-containing organic siloxane to ensure the processability and storage stability of the silicone rubber compound. In addition, the boron-containing organic siloxane improves the compatibility of methyl vinyl silicone rubber and methyl vinyl phenyl silicone rubber with porcelain-forming fillers and flame-retardant fillers, enhances the mechanical properties, and is conducive to processing and molding. The addition of a release agent reduces the phenomenon of silicone rubber compound sticking to the roller.

[0062] In a third aspect, the present invention provides the use of the silicone rubber compound described in the first aspect or the preparation method described in the second aspect in the preparation of ceramicized fireproof silicone rubber and fireproof rubber products.

[0063] In the silicone rubber system of the present invention, a composite ceramic filler containing copper oxide, titanium dioxide and gallium oxide, and a composite ceramic filler containing antimony trioxide and bismuth trioxide are used. During the heating process or when encountering combustion, antimony trioxide begins to melt into a liquid phase when it exceeds 655°C, filling between other fillers and silicon dioxide, and begins to "bridge" so that the burned silicon dioxide is closely connected to the surface of the fireproof material. Bismuth trioxide begins to melt above 825°C, forming more eutectics with antimony trioxide, forming a protective film on the surface of the material to isolate the air, and lowering the material temperature through the liquid phase. At a higher temperature of 1150°C, copper oxide will undergo liquid phase sintering to form a liquid film to reduce the sintering temperature of the ceramic. There is also an interaction between the ceramic filler and the flame retardant filler. The aluminum oxide generated by the pyrolysis of aluminum hydroxide reacts with titanium dioxide to sinter in a solid state to form Al2Ti7O 15 This reaction can increase the diffusion coefficient of the liquid film and promote grain growth. 15 Filling in the gaps of the ceramic body, while antimony trioxide, bismuth trioxide and copper oxide continuously form a eutectic, bismuth trioxide and copper oxide generate CuBiO4, promoting the formation of dense and continuous ceramics, and reducing the generation of pores. Further, at a high temperature of about 1700°C, β-phase gallium oxide has ultra-high heat and high temperature resistance, and fills the gaps in the ceramic layer at high temperature and the holes generated by the gasification of fillers with lower melting temperatures with high melting point alumina. Short-cut high-silica fibers tightly connect the ceramic layer on the surface of the fireproof material with the matrix, ensuring that the ceramic surface is dense and the ceramic interior is hard after ablation, forming a completely connected and high-strength flame-retardant and fire-resistant ceramic body, and improving the flame-retardant and fire-resistant properties of the material. In a high-temperature environment, the melting of the ceramic filler provides a large amount of liquid phase material to bond the surface of the residue more tightly and evenly, allowing the formation of more continuous phases, and the silicone rubber has higher mechanical strength after ceramicization.

[0064] In the present invention, a ceramic filler (compound of copper oxide, titanium dioxide and gallium oxide), a ceramic-aiding filler (compound of antimony trioxide and bismuth trioxide) and a boron-containing organic siloxane are used in combination to prepare a silicone rubber compound with high strength, high density and excellent processing performance and a ceramic fire-resistant silicone rubber.

[0065] In a fourth aspect, the present invention provides a ceramic fire-resistant silicone rubber, which is obtained by mixing and vulcanizing the silicone rubber compound described in the first aspect.

[0066] In a fifth aspect, the present invention provides a method for preparing the ceramic fire-resistant silicone rubber described in the fourth aspect, wherein the silicone rubber mixture described in the first aspect is refined in a double-roll mill, a vulcanizing agent is added, the roller spacing is shortened for thinning, the roller spacing is adjusted to flatten the rubber material, the obtained rubber material is placed in a tableting mold, the tableting mold is placed in a flat vulcanizer for one-stage vulcanization, and then two-stage vulcanization is performed to obtain the ceramic fire-resistant silicone rubber.

[0067] In the preparation method described in the fifth aspect, in one embodiment, the silicone rubber compound is rolled on a double-roll mill for 2 to 5 times.

[0068] In the preparation method described in the fifth aspect, the vulcanizing agent may be a peroxide vulcanizing agent.

[0069] In the preparation method described in the fifth aspect, the amount of the vulcanizing agent used can be 0.3% to 1.5% of the mass of the silicone rubber compound.

[0070] In the preparation method described in the fifth aspect, the first stage vulcanization is used to set the rubber material, and the second stage vulcanization is used to remove low-volatile substances in the silicone rubber compound and by-products generated during the vulcanization process of the vulcanizing agent.

[0071] In the preparation method described in the fifth aspect, the pressure of the first stage of vulcanization can be 5 to 15 MPa, the pressing temperature can be 110 to 180° C., and the time can be 10 to 20 minutes;

[0072] In the preparation method described in the fifth aspect, the temperature of the second-stage vulcanization can be 180-220° C., and the time can be 2-4 hours.

[0073] Compared with the prior art, the present invention has the following beneficial effects:

[0074] 1) The fireproof silicone rubber material prepared by the present invention achieves excellent mechanical properties at a relatively low addition amount by compounding a variety of ceramic fillers and ceramic-assisting fillers, and the ceramic has good strength after ablation.

[0075] 2) The fireproof silicone rubber material prepared by the present invention forms a hard, dense and complete ceramic body after being burned at a high temperature of 1600-1750°C. After being subjected to flame attack for 30 minutes, the ceramic body remains tight and hard and has high mechanical strength.

[0076] 3) The high-efficiency fireproof silicone rubber material prepared by the present invention has good plasticity and good processing and molding performance, can be used to produce various molded products and related extrusion products, and is suitable for continuous large-scale production.

[0077] 4) The raw materials and added fillers used in the present invention are halogen-free, non-toxic and low in smoke. DETAILED DESCRIPTION

[0078] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples that do not specify specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the "parts" in the following examples and comparative examples all refer to parts by mass.

[0079] Example 1

[0080] Step 1:

[0081] The preparation process of methyl-terminated boron-containing organosiloxane is as follows: add silane composed of methylphenyldimethoxysilane and dimethyldiethoxysilane in a molar ratio of 2:8 and toluene of 50% of the mass of silane to a three-necked flask equipped with a thermometer, a magnetic stirrer, a condenser and a constant pressure dropping funnel, and add a hydrochloric acid aqueous solution with a pH of 3-4 while stirring. The water content in the hydrochloric acid aqueous solution is 20% of the water required for the theoretical complete reaction of silane, and the reaction temperature is controlled to be 60°C and the reaction time is 4h. After the reaction is completed, the upper acid water is separated, toluene of 50% of the mass of silane is added, and phenylboric acid with a molar ratio of 1:3 to silane and hexamethyldisiloxane with a molar ratio of 0.04:1 to silane are added to the above three-necked flask for reaction, and the reaction temperature is controlled to be 80°C and the reaction time is 6h. After the reaction is completed, wash with water and separate the layers. Take the organic phase and finally remove the toluene solvent under vacuum at 70°C to obtain a methyl-terminated boron-containing organosiloxane.

[0082] The hydroxyl-terminated boron-containing organosiloxane is obtained without adding hexamethyldisiloxane in the above preparation process.

[0083] Step 2: 40 parts of a vinyl molar content of 0.12% and a molecular weight of 48×10 4 g / mol methyl vinyl silicone rubber raw rubber, 40 parts of vinyl molar content of 0.24%, molecular weight of 72×10 4 g / mol methyl vinyl silicone rubber raw rubber, 20 parts of vinyl molar content of 0.2%, phenyl molar content of 30%, molecular weight of 40×10 4 g / mol methyl vinyl phenyl silicone rubber raw rubber, 12 parts specific surface area is 130m 2 / g of precipitated silica, 18 parts with a specific surface area of ​​180m 2 / g of precipitated silica and 5 parts of hydroxy silicone oil with a hydroxyl content of 6% are added to a kneader for internal mixing. The silica is added in multiple batches. After the last batch of filler is added, internal mixing is continued for 40 minutes to ensure that the rubber is evenly mixed.

[0084] Step 3: 4 parts of copper oxide, 9 parts of titanium dioxide, 4 parts of antimony trioxide, 4 parts of bismuth trioxide, 7 parts of gallium oxide, 20 parts of aluminum hydroxide, 6 parts of hydroxyl-terminated boron-containing organosiloxane prepared in step 1, 4 parts of methyl-terminated boron-containing organosiloxane prepared in step 1, 0.15 parts of zinc stearate, and 2 parts of 1 mm short-cut high-silica fiber are added to a kneader for internal kneading. Porcelain-forming fillers, porcelain-aiding fillers, and aluminum hydroxide are added in multiple batches, and the internal kneading is continued for 40 minutes after the last batch of fillers is added.

[0085] Step 4: Raise the temperature of the kneading machine cabin to 150°C, perform constant temperature kneading for 60 minutes under a negative pressure environment of -0.05 MPa, then maintain the vacuum and start cooling for 30 minutes, and obtain the silicone rubber compound after cooling.

[0086] Step 5: Take the silicone rubber compound that has been standing for more than 12 hours at room temperature and roll it on a two-roll mill for 3 times, add 0.7% of the mass of the silicone rubber compound 2,4-dichloroperoxide benzoyl vulcanizer, and then thin it twice, adjust the roller distance to roll the rubber flat. Then put the rubber into a tableting mold, and the tableting mold is placed in a flat vulcanizer, and vulcanize it at 14MPa and 170℃ for 12 minutes, and finally vulcanize it at 210℃ for 120 minutes to obtain ceramic fire-resistant silicone rubber.

[0087] Example 2

[0088] The only difference from Example 1 is that in step 3, the amount of copper oxide added is 5 parts and the amount of titanium dioxide added is 11 parts, and the rest are the same.

[0089] Example 3

[0090] The only difference from Example 1 is that the amount of gallium oxide added in step 3 is 10 parts, and the rest is the same.

[0091] Example 4

[0092] The only difference from Example 1 is that in step 3, the amount of antimony trioxide added is 8 parts, and the rest is the same.

[0093] Example 5

[0094] The only difference from Example 1 is that in step 3, 8 parts of bismuth trioxide are added, and the rest are the same.

[0095] Example 6

[0096] The only difference from Example 1 is that in step 3, the amount of hydroxyl-terminated boron-containing polysiloxane added is 5 parts, and the amount of methyl-terminated boron-containing polysiloxane added is 7 parts, and the rest are the same.

[0097] Example 7

[0098] Step 1: Same as step 1 in Example 1.

[0099] Step 2: 45 parts of a vinyl molar content of 0.04% and a molecular weight of 48×10 4 g / mol methyl vinyl silicone rubber raw rubber, 40 parts of vinyl molar content of 0.12%, molecular weight of 62×10 4 g / mol methyl vinyl silicone rubber raw rubber, 15 parts of vinyl molar content of 0.4%, phenyl molar content of 35%, molecular weight of 50×10 4g / mol methyl vinyl phenyl silicone rubber raw rubber, 15 parts specific surface area is 130m 2 / g of precipitated silica, 15 parts with a specific surface area of ​​180m 2 / g of precipitated silica and 6 parts of hydroxy silicone oil with a hydroxyl content of 4% are added to a kneader for internal mixing. The silica is added in multiple batches. After the last batch of filler is added, the internal mixing is continued for 50 minutes to ensure that the rubber is evenly mixed.

[0100] Step 3: 4 parts of copper oxide, 10 parts of titanium dioxide, 4.5 parts of antimony trioxide, 4.5 parts of bismuth trioxide, 11 parts of gallium oxide, 20 parts of aluminum hydroxide, 7 parts of hydroxyl-terminated boron-containing organosiloxane prepared in step 1, 3 parts of methyl-terminated boron-containing organosiloxane prepared in step 1, 0.18 parts of zinc stearate and 5 parts of 2mm short-cut high-silica fiber are added to a kneader for internal mixing. Porcelain-forming fillers, porcelain-aiding fillers and aluminum hydroxide are added in multiple batches, and the internal mixing is continued for 60 minutes after the last batch of fillers is added.

[0101] Step 4: Raise the temperature of the kneading machine cabin to 140°C, perform constant temperature kneading for 60 minutes under a negative pressure environment of -0.05 MPa, then maintain the vacuum and start cooling for 20 minutes, and obtain the silicone rubber compound after cooling.

[0102] Step 5: Take the silicone rubber compound that has been standing for more than 12 hours at room temperature and roll it on a double-roll mill for 3 times, add 0.7% of the mass of the silicone rubber compound 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane vulcanizer, and then thin it twice, adjust the roller distance to roll the rubber flat. Then put the rubber into a tableting mold, and place the tableting mold in a flat vulcanizer, vulcanize it at 13MPa and 175℃ for 10 minutes, and finally vulcanize it at 200℃ for 120 minutes to obtain ceramic fire-resistant silicone rubber.

[0103] Example 8

[0104] Step 1: Same as step 1 in Example 1.

[0105] Step 2: 25 parts of a vinyl molar content of 0.12% and a molecular weight of 48×10 4 g / mol methyl vinyl silicone rubber raw rubber, 65 parts of vinyl molar content of 0.24%, molecular weight of 72×10 4 g / mol methyl vinyl silicone rubber raw rubber, 30 parts of vinyl molar content of 0.35%, phenyl molar content of 40%, molecular weight of 70×10 4 g / mol methyl vinyl phenyl silicone rubber raw rubber, 15 parts specific surface area is 130m 2 / g of precipitated silica, 15 parts with a specific surface area of ​​180m 2 / g of precipitated silica and 4 parts of hydroxy silicone oil with a hydroxyl content of 8% are added to a kneader for internal mixing. The silica is added in multiple batches. After the last batch of filler is added, internal mixing is continued for 40 minutes to ensure that the rubber is evenly mixed.

[0106] Step 3: 4 parts of copper oxide, 8 parts of titanium dioxide, 3 parts of antimony trioxide, 3 parts of bismuth trioxide, 6 parts of gallium oxide, 25 parts of aluminum hydroxide, 5 parts of hydroxyl-terminated boron-containing organosiloxane prepared in step 1, 3 parts of methyl-terminated boron-containing organosiloxane prepared in step 1, 0.16 parts of zinc stearate and 3 parts of 4mm short-cut high-silica fiber are added to a kneader for internal mixing. Porcelain-forming fillers, porcelain-aiding fillers and aluminum hydroxide are added in multiple batches, and the internal mixing is continued for 45 minutes after the last batch of fillers is added.

[0107] Step 4: Raise the temperature of the kneading machine cabin to 160°C, perform constant temperature kneading for 60 minutes under a negative pressure environment of -0.06 MPa, then maintain the vacuum and start cooling for 30 minutes, and obtain the silicone rubber compound after cooling.

[0108] Step 5: Take the silicone rubber compound that has been standing for more than 12 hours at room temperature and roll it on a double-roll mill for 3 times, add 0.7% of the mass of the silicone rubber compound 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane vulcanizer, and then thin it twice, adjust the roller distance to roll the rubber flat. Then put the rubber into a tableting mold, and place the tableting mold in a flat vulcanizer, vulcanize it at 15MPa and 180℃ for 10 minutes, and finally vulcanize it at 200℃ for 120 minutes to obtain ceramic fire-resistant silicone rubber.

[0109] Comparative Example 1

[0110] The only difference from Example 1 is that antimony trioxide and bismuth trioxide are not added, and the rest are the same.

[0111] Comparative Example 2

[0112] The only difference from Example 1 is that the boron-containing organosiloxane is replaced by 10 parts of boric acid, and the rest is the same.

[0113] Comparative Example 3

[0114] The only difference from Example 7 is that gallium oxide is not added, and the rest is the same.

[0115] Comparative Example 4

[0116] The only difference from Example 7 is that copper oxide, titanium dioxide and short-cut high-silica fibers are not added, and the rest are the same.

[0117] Performance inspection test

[0118] The ceramic fireproof silicone rubber obtained by vulcanizing the silicone rubber compound initially prepared as described in the above embodiments and comparative examples and the ceramic body obtained by ablation thereof were tested for performance, and the test standards were as follows:

[0119] (1) Density: The density of ceramic bodies under high temperature conditions is tested according to the standard GB / T 25995-2010 precision ceramic density and apparent porosity test method, with a sample mass of 10 g and an accuracy of 0.1 mg. Each sample is measured at least twice to ensure the reproducibility of the measurement results.

[0120] (2) Flame retardancy: According to the standard GB / T 10707-2008 for the determination of rubber combustion performance, a vertical combustion test was conducted. The sample length was 130 mm ± 5 mm, the width was 13.0 mm ± 0.5 mm, and the height was 3.0 mm ± 0.25 mm. The sample was vertically supported, and the flame was applied for 10 s ± 0.5 s. The flame was removed and the stopwatch was started at the same time, and the flaming combustion time t1 was recorded. When the flame of the sample was extinguished, the flame was immediately applied again, and the flame was removed after 10 s ± 0.5 s. The flaming combustion time t2 and the flameless combustion time t g .

[0121] (3) Ablation resistance: Use acetylene flame with oxygen at about 1700°C for 30 minutes to observe whether there are cracks or burn-through on the surface. The sample thickness is 2 mm.

[0122] (4) Tensile tear test: According to GB / T 528-2009, tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, dumbbell-shaped specimens are used to test the tensile properties of the material, and right-angle tear specimens are used to test the tear properties of the material. When cutting the specimen, place the cutter vertically above the film, and rotate the punch to cut the specimen. During the test, clamp the two ends of the specimen between the upper and lower clamps of the tensile testing machine, set the tensile speed to 500mm / min, start the testing machine, and the machine applies a gradually increasing traction force to the specimen until the specimen breaks. Finally, the machine gives the material-related tensile and tear parameter data. Cut five tensile specimens and four tear specimens for each rubber material, and take the average value after testing.

[0123] (5) Bending strength test: According to GB / T 6569-2006 fine ceramic bending strength test method, the specimen is 50 mm × 4 mm × 3 mm.

[0124] The performance test results of the ceramic silicone rubber provided in the above embodiments and comparative examples are shown in Table 1 below.

[0125] Table 1 Test results of ceramic silicone rubber performance parameters at room temperature

[0126]

[0127] Table 2 Test results of ceramic silicone rubber performance parameters after flame impact

[0128]

[0129] According to the data of the embodiment in Table 1, the ceramic fire-resistant silicone rubber prepared in the present invention has good tensile strength, tear strength and elongation at break, and a continuous, dense and hard ceramic body can be obtained after ablation, and has good mechanical strength.

[0130] In Examples 1 to 8, ceramic fillers (antimony oxide, bismuth trioxide, copper oxide, titanium dioxide, and gallium oxide are compounded) and boron-containing organosiloxanes are added in batches, and have good compatibility, plasticity, and processing properties during the actual processing; when the amount of ceramic fillers is increased simultaneously within the proportional range, the tensile strength of the silicone rubber compound is higher, and the density and bending strength of the ceramic body after ablation are also higher; the ceramic effect of using a variety of ceramic fillers in combination is better than that of using any one of the fillers alone.

[0131] In Comparative Example 1, no antimony trioxide and bismuth trioxide were added, and a good fireproof ceramic layer could not be formed when attacked by a relatively low-temperature flame. SiO2 fell off, resulting in poor ceramic density when impacted by a high-temperature flame, and the ceramic integrity of the obtained ceramic fireproof silicone rubber material was poor.

[0132] In Comparative Example 2, the boron-containing organosiloxane of the present invention was not added, and the silicone rubber compound had a roller sticking phenomenon during the kneading process, and the plasticity was poor. After ablation, fine cracks existed in the ceramic body, and a dense and hard ceramic body could not be formed.

[0133] Comparative Example 3 does not add gallium oxide. Under the impact of a flame at 1700°C, there is not enough high-temperature resistant filler to fill the gaps between the ceramic layers in time, and the low melting temperature filler vaporizes, resulting in poor ablation resistance of the ceramicized fireproof silicone rubber material.

[0134] Comparative Example 4 does not add copper oxide and titanium dioxide. Although antimony trioxide and bismuth trioxide will melt at high temperature and leave SiO2, there is no connection and support function of short-cut high-silica fibers, resulting in poor strength of the ceramic body, which will fall off under continuous flame impact, causing the ceramicized fire-retardant silicone rubber material to have poor fire retardant properties.

[0135] The flame retardant and fireproof silicone rubber material provided by the present invention is compounded with a variety of ceramic fillers and ceramic-aiding fillers, which can reduce the amount of fillers while still having excellent fire retardancy and good mechanical properties. It will not burn through under high-temperature flame ablation at 1600-1750°C for at least 30 minutes and still maintain a hard, dense and complete ceramic layer.

[0136] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A highly effective fireproof silicone rubber compound, characterized in that: In terms of mass fraction, the raw material composition includes: The porcelain-forming filler comprises: 3-9 parts of copper oxide, 5 to 12 parts of titanium dioxide, 4-12 parts of gallium oxide; The porcelain-aiding filler comprises: 3-15 parts of antimony trioxide, 3-15 parts of bismuth trioxide; The flame retardant filler includes aluminum hydroxide; The high temperature resistant fiber comprises short chopped high silica fiber; the short chopped high silica fiber is a glass fiber containing more than 95wt% of silica and having a length of 1 to 12mm; The preparation method of the boron-containing organosiloxane comprises the steps of: (1) adding acid water with a pH value of 3 to 4 to a mixed solution of silane and toluene, and reacting at 50 to 70° C.; the water content in the acid water is 15% to 30% of the amount of water required for the theoretical complete reaction of the silane; the silane comprises methylphenyldimethoxysilane and dimethyldiethoxysilane; the molar percentage of the methylphenyldimethoxysilane in the silane is 15% to 25%, and the molar percentage of the dimethyldiethoxysilane in the silane is 75% to 85%; (2) After the reaction in step (1) is completed, the upper layer of acid water is removed, and then toluene, phenylboric acid and hexamethyldisiloxane which may be optionally added are added, and the reaction is carried out at 70-90° C. After the reaction is completed, the layers are washed with water, and the organic phase is taken and distilled under reduced pressure to remove the solvent to obtain the boron-containing organic siloxane; the molar ratio of the added phenylboric acid to the silane is 1:1-4.

2. The silicone rubber compound according to claim 1, characterized in that: The sum of the mass fractions of copper oxide, titanium dioxide and gallium oxide is 15 to 30 parts; The sum of the mass fractions of antimony trioxide and bismuth trioxide is 6 to 24 parts.

3. The silicone rubber compound according to claim 1, characterized in that: In the preparation method of the boron-containing organosiloxane: In step (1), in the mixed solution of silane and toluene, the mass of toluene is 40% to 60% of the mass of silane; In step (1), the reaction time is 3 to 5 hours; In step (2), the mass of toluene added is 40% to 60% of the mass of the silane; In step (2), the molar ratio of the added phenylboric acid to the silane is 1:1 to 3; In step (2), the molar ratio of the added hexamethyldisiloxane to the silane is 0 to 0.05:1; In step (2), the temperature of the reduced pressure distillation is 60-80°C.

4. The silicone rubber compound according to claim 1, characterized in that: The vinyl content in the methyl vinyl silicone rubber is 0.03% to 3%; the molecular weight of the methyl vinyl silicone rubber is 45×10 4 ~85×10 4 g / mol; The molar content of vinyl in the methyl vinyl phenyl silicone rubber is 0.1% to 0.5%, and the molar content of phenyl is 30% to 40%; the molecular weight of the methyl vinyl phenyl silicone rubber is 40×10 4 ~80×10 4 g / mol; The white carbon black is precipitated white carbon black and / or gas phase white carbon black, and the specific surface area is 120 to 420 m 2 / g; The structure control agent includes hydroxy silicone oil; the hydroxyl mass content of the hydroxy silicone oil is 4% to 10%; The release agent includes a stearic acid compound.

5. The silicone rubber compound according to claim 4, characterized in that: The specific surface area of ​​the white carbon black is 120 to 220 m 2 / g.

6. The silicone rubber compound according to claim 4, characterized in that: The hydroxyl mass content of the hydroxy silicone oil is 4% to 8%.

7. The method for preparing a silicone rubber compound according to any one of claims 1 to 6, characterized in that: Includes steps: S1, adding methyl vinyl silicone rubber, methyl vinyl phenyl silicone rubber, white carbon black and a structure control agent into a kneader for internal kneading; S2, adding porcelain-forming filler, porcelain-assisting filler, flame-retardant filler, high-temperature resistant fiber, boron-containing organic siloxane and release agent for internal mixing; S3, raising the temperature of the kneading machine cabin to 80-160°C, kneading and mixing at a constant temperature under a negative pressure environment of -0.03-0.08 MPa to obtain the silicone rubber compound.

8. The method for preparing a silicone rubber compound according to claim 7, characterized in that: In step S1, white carbon black is added to the kneader in batches multiple times; The mixing time in step S1 is 40 to 90 minutes; The mixing time in step S2 is 40 to 120 minutes; In step S3, after the temperature of the kneading machine cabin is raised to 80-160° C., the constant temperature kneading time is 60-80 minutes.

9. Use of the silicone rubber compound according to any one of claims 1 to 6 or the preparation method according to claim 7 or 8 in the preparation of ceramic fireproof silicone rubber and fireproof rubber products.

10. A ceramic fireproof silicone rubber, characterized in that: The ceramic fireproof silicone rubber is obtained by mixing and vulcanizing the silicone rubber compound according to any one of claims 1 to 6.

11. The method for preparing ceramic fire-resistant silicone rubber according to claim 10, characterized in that: The silicone rubber compound described in any one of claims 1 to 6 is milled in a two-roll mill, a vulcanizing agent is added, the roller distance is shortened for thin-passing, the roller distance is adjusted to roll the rubber compound flat, the obtained rubber compound is placed in a tableting mold, the tableting mold is placed in a flat vulcanizer for one-stage vulcanization, and then two-stage vulcanization is performed to obtain the ceramicized fire-resistant silicone rubber.

12. The method for preparing ceramic fire-resistant silicone rubber according to claim 11, characterized in that: The silicone rubber compound is rolled on a double-roll mill for 2 to 5 times; The vulcanizing agent is a peroxide vulcanizing agent; the amount of the vulcanizing agent is 0.3% to 1.5% of the mass of the silicone rubber compound; The pressure of the first stage vulcanization is 5-15MPa, the pressing temperature is 110-180°C, and the time is 10-20 minutes; The temperature of the second stage vulcanization is 180-220° C., and the time is 2-4 hours.

Citation Information

Patent Citations

  • Ceramic flame-retardant heat-insulating fireproof material and preparation method and application thereof

    CN113829701A

  • Flame-retardant heat-insulation fireproof material for battery

    CN115538175A

  • Ceramic silicon rubber and preparation method thereof

    CN106046797A

  • Water-based borosilicon rubber ceramic composite material, and preparation method and application thereof

    CN108929545A